Kidney Structure of Pangasianodon hypophthalmus Fed with Fermented Red Ginger and Infection by Aeromonas hydrophila - Morina Riauwaty; Windarti Windarti; Mariani Natalina Linggasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Red ginger contain antioxidant that can be used to enhance the immune system of fish. A study was conducted from September to December 2021 to understand the kidney structure of Pangasianodon hypophthalmus that fed with red ginger fermented pellets. The fermented red ginger juice was obtained by juicing 500 g of red ginger in 3L water, boiled and mixed with 175 ml molasses, 65 ml yogurt and 50 mg yeast and then was fermented for seven days. The fermented red ginger juice was obtained by juicing 500 g of red ginger in days. The fermented red ginger juice was mixed with fish feed pellets, namely T1 (150 mL/Kg), T2 (175 mL/Kg), T3 (200 mL/Kg), Cn (no red ginger juice and no infection), Cp (no red ginger juice and infection by A. hydrophila). The fish were reared in 30L aquaria. Fish sample was P. hypophthalmus fingerling (10-12 cm and 5-7 g), 10 fishes/aquarium. The fish were fed 3 time a day, adlibitum. In the 30th day, A. hydrophila was injected to the treated fish (0.1.ml of 108 cells/ml, subcutan injection). In the 14th after the infection kidney sample was collected and processed for histological study. Result shown that there were differences in kidney tissue of fish in each treatment. The worst condition was obtain in Cp, while the best was in T2. The renal structure of Cp showed abnormalities such as hemorrhage, cell necrosis, enlarged Bowman's cyst, and tubular degeneration, while the T2 kidney showed mild lesions specifically haemorrhagic. This fact indicates that fermented red ginger can improve fish immunity against A. hydrophila infection